Visible spectrophotometric Methods for Estimation of Tizanidine from Bulk Drug and Formulation - Ravi, Dubbaka; Malli Patil, S.M.; Appala Raju, S. (Asian Journal of Chemistry, 2010)
Three simple acid-dye colorimetric methods for estimation of tizanidine, 5-chloro-N-(4,5-dihydro-1H-imidazol-2-yl) 2,1,3- benzothiadiazol derivative which is mainly used as a centrally acting skeletal muscle relaxant, have been developed. The developed methods involve formation of coloured chloroform extractable complexes of drug with bromocresol purple, bromocresol green and bromophenol blue in acidic medium. Extracted complexes showed absorption maxima at 417 nm, 415 nm and 414 nm and showed linearity in concentration ranges of 2-10 mcg/mL, 4-20 mcg/mL and 2-10 mcg/mL respectively. Results were validated statistically and were found to be reproducible.